Origanum majorana Ethanolic Extract Promotes Colorectal Cancer Cell Death by Triggering Abortive Autophagy and Activation of the Extrinsic Apoptotic Pathway - Benhalilou, Nehla; Alsamri, Halima; Alneyadi, Aysha; Athamneh, Khawlah; Alrashedi, Asma; Altamimi, Nedaa; Al Dhaheri, Yusra; Eid, Ali H.; Iratni, Rabah (Frontiers in Oncology, 2019)
Colorectal cancer is the third leading cause of cancer-related death worldwide. We have previously shown that Origanum majorana ethanolic extract (OME) promoted mitotic arrest, induced apoptosis and inhibited migration, metastasis and tumor growth of triple negative breast cancer. Here, we investigated the potential anticancer effect and the molecular mechanism of Origanum majoran ethanolic extract against human colorectal cancer cells. Our results showed that OME exhibited strong anti-proliferative activity against colorectal cancer cells (HT-29 and Caco-2) in a concentration- and time-dependent manner. OME inhibited cell viability, colony growth and induced mitotic arrest of HT-29 cells. Also, OME induced DNA damage, triggered abortive autophagy and activated a caspase 3 and 7-dependent extrinsic apoptotic pathway, most likely through activation of the TNFα pathway. Time-course analysis revealed that DNA damage occurred concomitantly with abortive autophagy after 4 hours post-OME treatment while apoptosis was activated only 24 hours later. Blockade of autophagy initiation, by 3-methyladenine, reduced OME-induced cell death while inhibition of apoptosis had a minimal effect. We also found that OME downregulated survivin in HT-29 cells. Our findings demonstrate that Origanum majorana extract possesses strong anti-colon cancer activity through induction of autophagic and apoptotic cell death, making it a potential and valuable source of novel therapeutic cancer agents.